The relation between knee muscle strength and performance tests in orienteering athletes - Cinar-Medeni, Ö.; Colakoglu, F. F.; Yüce, K.; Ipekoglu, G.; Baltaci, G. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of this study was to analyze the effect of knee muscle strength on performance tests in orienteers.